Developmental regulation of chromatin conformation by Hox proteins in Drosophila. - Agelopoulos, M.; McKay, D.J.; Mann, R.S. (Cell reports, 2012)
We present a strategy to examine the chromatin conformation of individual loci in specific cell types during Drosophila embryogenesis. Regulatory DNA is tagged with binding sites (lacO) for LacI, which is used to immunoprecipitate the tagged chromatin from specific cell types. We applied this approach to Distalless (Dll), a gene required for limb development in Drosophila. We show that the local chromatin conformation at Dll depends on the cell type: in cells that express Dll, the 5' regulatory region is in close proximity to the Dll promoter. In Dll-nonexpressing cells this DNA is in a more extended configuration. In addition, transcriptional activators and repressors are bound to Dll regulatory DNA in a cell type-specific manner. The pattern of binding by GAGA factor and the variant histone H2Av suggest that they play a role in the regulation of Dll chromatin conformation in expressing and nonexpressing cell types, respectively.